Tag: Arden’s Method

DFA to Regular Expression | Arden’s Theorem

DFA to Regular Expression-

 

The two popular methods for converting a given DFA to its regular expression are-

 

 

  1. Arden’s Method
  2. State Elimination Method

 

In this article, we will discuss Arden’s Theorem.

 

Arden’s Theorem-

 

Arden’s Theorem is popularly used to convert a given DFA to its regular expression.

 

It states that-

Let P and Q be two regular expressions over ∑.

If P does not contain a null string ∈, then-

R = Q + RP has a unique solution i.e. R = QP*

 

Conditions-

 

To use Arden’s Theorem, following conditions must be satisfied-

  • The transition diagram must not have any ∈ transitions.
  • There must be only a single initial state.

 

Steps-

 

To convert a given DFA to its regular expression using Arden’s Theorem, following steps are followed-

 

Step-01:

 

  • Form a equation for each state considering the transitions which comes towards that state.
  • Add ‘∈’ in the equation of initial state.

 

Step-02:

 

Bring final state in the form R = Q + RP to get the required regular expression.

 

Important Notes-

 

Note-01:

 

Arden’s Theorem can be used to find a regular expression for both DFA and NFA.

 

Note-02:

 

If there exists multiple final states, then-

  • Write a regular expression for each final state separately.
  • Add all the regular expressions to get the final regular expression.

 

Also Read- State Elimination Method

 

PRACTICE PROBLEMS BASED ON CONVERTING DFA TO REGULAR EXPRESSION-

 

Problem-01:

 

Find regular expression for the following DFA using Arden’s Theorem-

 

 

Solution-

 

Step-01:

 

Form a equation for each state-

  • A = ∈ + B.1     ……(1)
  • B = A.0           ……(2)

 

Step-02:

 

Bring final state in the form R = Q + RP.

 

Using (1) in (2), we get-

B = (∈ + B.1).0

B = ∈.0 + B.1.0

B = 0 + B.(1.0)          ……(3)

 

Using Arden’s Theorem in (3), we get-

B = 0.(1.0)*

 

Thus, Regular Expression for the given DFA = 0(10)*

 

Problem-02:

 

Find regular expression for the following DFA using Arden’s Theorem-

 

 

Solution-

 

Step-01:

 

Form a equation for each state-

  • q1 = ∈                                        ……(1)
  • q2 = q1.a                                   ……(2)
  • q3 = q1.b + q2.a + q3.a            …….(3)

 

Step-02:

 

Bring final state in the form R = Q + RP.

 

Using (1) in (2), we get-

q2 = ∈.a

q2 = a              …….(4)

 

Using (1) and (4) in (3), we get-

 

q3 = q1.b + q2.a + q3.a

q3 = ∈.b + a.a + q3.a

q3 = (b + a.a) + q3.a        …….(5)

 

Using Arden’s Theorem in (5), we get-

q3 = (b + a.a)a*

 

Thus, Regular Expression for the given DFA = (b + aa)a*

 

Problem-03:

 

Find regular expression for the following DFA using Arden’s Theorem-

 

 

Solution-

 

Step-01:

 

Form a equation for each state-

  • q1 = ∈ + q1.b + q2.a                 ……(1)
  • q2 = q1.a + q2.b                       ……(2)

 

Step-02:

 

Bring final state in the form R = Q + RP.

 

Using Arden’s Theorem in (2), we get-

q2 = q1.a.b*             …….(3)

 

Using (3) in (1), we get-

q1 = ∈ + q1.b + q1.a.b*.a

q1 = ∈ + q1.(b + a.b*.a)          …….(4)

 

Using Arden’s Theorem in (4), we get-

q1 = ∈.(b + a.b*.a)*

q1 = (b + a.b*.a)*

 

Thus, Regular Expression for the given DFA = (b + a.b*.a)*

 

Problem-04:

 

Find regular expression for the following DFA using Arden’s Theorem-

 

 

Solution-

 

Step-01:

 

Form a equation for each state-

  • q1 = ∈ + q1.a + q3.a                 ……(1)
  • q2 = q1.b + q2.b + q3.b            ……(2)
  • q3 = q2.a                                  …….(3)

 

Step-02:

 

Bring final state in the form R = Q + RP.

 

Using (3) in (2), we get-

q2 = q1.b + q2.b + q2.a.b

q2 = q1.b + q2.(b + a.b)          …….(4)

 

Using Arden’s Theorem in (4), we get-

q2 = q1.b.(b + a.b)*    …….(5)

 

Using (5) in (3), we get-

q3 = q1.b.(b + a.b)*.a       …….(6)

 

Using (6) in (1), we get-

q1 = ∈ + q1.a + q1.b.(b + a.b)*.a.a

q1 = ∈ + q1.(a + b.(b + a.b)*.a.a)        …….(7)

 

Using Arden’s Theorem in (7), we get-

q1 = ∈.(a + b.(b + a.b)*.a.a)*

q1 = (a + b.(b + a.b)*.a.a)*

 

Thus, Regular Expression for the given DFA = (a + b(b + ab)*aa)*

 

Also Read- Minimization of DFA

 

To gain better understanding about Arden’s Theorem,

Watch this Video Lecture

 

Next Article- Non-Deterministic Finite Automata

 

Get more notes and other study material of Theory of Automata and Computation.

Watch video lectures by visiting our YouTube channel LearnVidFun.